Vocational Career Guidance and Counselling in Schools (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
This article provides an overview of the importance of vocational career guidance and counselling in schools. It discusses the need for early career planning and exploration, as well as the role of school counsellors in helping students identify their strengths, interests, and career goals. The article highlights various vocational assessment tools and resources that can be used to support career exploration, and emphasizes the importance of providing students with exposure to different career options through job shadowing,internships, and other experiential learning opportunities. Additionally, the article emphasizes the importance of building partnerships between schools, employers, and other community stakeholders to ensure that students receive comprehensive vocationalguidance and support. Overall, this article underscores the critical role that vocational career guidance and counselling play in helping students make informed decisions about their futures and achieve their career aspirations.